Non-negative matrix factorization for medical imaging - Stoean, Ruxandra; Atencia-Ruiz, Miguel Alejandro (i6doc.com, 2018)
A non-negative matrix factorization approach to dimensionality reduction is proposed to aid classification of images. The original images can be stored as lower-dimensional columns of a matrix that hold degrees of belonging to feature components, so they can be used in the training phase of the classification at lower runtime and without loss in accuracy. The extracted features can be visually examined and images reconstructed with limited error. The proof of concept is performed on a benchmark of handwritten digits, followed by the application to histopathological colorectal cancer slides. Results are encouraging, though dealing with real-world medical data raises a number of issues.
Keywords: Matemáticas aplicadas - Congresos